2007
DOI: 10.1248/bpb.30.845
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fermented Soybean (Natto) Increased Locomotor Activity in Mice

Abstract: We fed mice food granules containing fermented soybean (natto in Japanese) powder (hereafter "natto granules") for 14 d to investigate whether natto granules had any effects on mouse behavior. We noted an enhancement of locomotor activity in natto-granule-fed mice compared to control and soybean-pelletfed mice. This enhanced locomotor activity was blocked by a low dose of haloperidol (1 m mg/kg i.p.), a dopamine receptor antagonist, but not by methysergide, a serotonin 5-HT 1/2 receptor antagonist. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As an example a subtilisin-like serine protease, nattokinase, has been reported to have pro-fribrinolitic effect in in vivo and in vitro studies (Fujita et al 1993;Pais et al 2006;Sumi et al 1987). Mamiya and Nishimura (2007) reported enhancement of locomotor activity in mice fed with natto. Natto intake has also been reported to support bone formation in menopausal women and to prevent postmenopausal bone loss possibly due to the presence of menaquinone or bioavailable isoflavones in natto (Ikeda et al 2006;Katsuyama et al 2004).…”
Section: Nattomentioning
confidence: 99%
See 1 more Smart Citation
“…As an example a subtilisin-like serine protease, nattokinase, has been reported to have pro-fribrinolitic effect in in vivo and in vitro studies (Fujita et al 1993;Pais et al 2006;Sumi et al 1987). Mamiya and Nishimura (2007) reported enhancement of locomotor activity in mice fed with natto. Natto intake has also been reported to support bone formation in menopausal women and to prevent postmenopausal bone loss possibly due to the presence of menaquinone or bioavailable isoflavones in natto (Ikeda et al 2006;Katsuyama et al 2004).…”
Section: Nattomentioning
confidence: 99%
“…African and Asian alkaline condiments often have numerous advantages over the raw materials from which they are made (Addy et al 1995;Ko et al 2004;Igboeli et al 1997;Mamiya et al 2007;Nnam et al 2003;Pais et al 2006;Sarkar et al 1997b;Sarkar et al 1998). The fermentation can simultaneously create or improve flavor and texture, appearance, aroma and nutritional status, destroy or mask undesirable flavors, reduce or eliminate carbohydrates causing flatulence, decrease the required cooking time and increase shelf life (Wang and Fung 1996;Steinkraus 1996).…”
Section: Indigenous Alkaline-fermented Condiments As Functional Foodsmentioning
confidence: 99%
“…Several studies on the health benefits of natto have been conducted; furthermore, in vivo and in vitro studies have demonstrated that serine proteases such as subtilisin and nattokinase have a profibrinolytic effect [26][27][28]. Mamiya and Nishimura [29] found that rats fed with natto had enhanced locomotor activity. Natto has some amazing benefits for bone development in menopausal women and postmenopausal bone loss prevention, which is most likely due to the presence of menaquinones or non-nato flavones in natto [30,31].…”
Section: Nutritional Compositionmentioning
confidence: 99%